2018
DOI: 10.1002/nbm.3915
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral perfusion characteristics show differences in younger versus older children with sickle cell anaemia: Results from a multiple‐inflow‐time arterial spin labelling study

Abstract: Sickle cell anaemia (SCA) is associated with chronic anaemia and oxygen desaturation, which elevate cerebral blood flow (CBF) and increase the risk of neurocognitive complications. Arterial spin labelling (ASL) provides a methodology for measuring CBF non-invasively; however, ASL techniques using only a single inflow time are not sufficient to fully characterize abnormal haemodynamic behaviour in SCA. This study investigated haemodynamic parameters from a multi-inflow-time ASL acquisition in younger (8-12 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 43 publications
3
7
0
Order By: Relevance
“…23,24,45 Although the T1 tissue value used is likely too high for the gray and white matter ROIs, this will not have affected the fitted BAT values, and would only have had a small effect on the fitted CBF values. Whilst the absolute fitted values in these regions should therefore be interpreted with caution, and were higher than those based on the singleTI sequence and prior multiTI ASL work in gray matter, 31,32 the key comparisons were in the same direction and overall agreement. Importantly, the strength of correlations between CBF values and other parameters will not have been impacted.…”
Section: Limitationsmentioning
confidence: 65%
See 2 more Smart Citations
“…23,24,45 Although the T1 tissue value used is likely too high for the gray and white matter ROIs, this will not have affected the fitted BAT values, and would only have had a small effect on the fitted CBF values. Whilst the absolute fitted values in these regions should therefore be interpreted with caution, and were higher than those based on the singleTI sequence and prior multiTI ASL work in gray matter, 31,32 the key comparisons were in the same direction and overall agreement. Importantly, the strength of correlations between CBF values and other parameters will not have been impacted.…”
Section: Limitationsmentioning
confidence: 65%
“…blood) arrival times (BAT) across the whole brain 31 and in anterior, middle, and posterior cerebral artery territories, consistent with macrocirculatory hyperperfusion leading to faster transit times. 32 However, these studies only examined hemodynamic parameters in gray matter. Further, no ASL study (cross-sectional or longitudinal) has attempted to quantify CBF or BAT from venous signal, or assess associations with cognition in an SCA population.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could be especially valuable in patients with SCD, as SCD is known to affect both large and small blood vessels. In SCD, ATT was found to be reduced compared to healthy controls (Juttukonda et al, 2017;Kawadler et al, 2018) under resting conditions. However, no studies to date have reported ATT changes in response to a cerebral vasodilatory challenge.…”
Section: Introductionmentioning
confidence: 79%
“…To combat these challenges, some authors have advocated for correction for labeling efficiency, along with the employment of two-compartment models, but further work on the validity of ASL kinetic models in SCD patients is required. Acquisitions with multiple inflow times [ 137 , 138 ] do not require prior assumptions about the necessary delay for the fully labeled bolus of blood to arrive and allow for further characterization of hemodynamic behavior within a voxel, though there have been relatively few studies in this population [ 137 ]. Overall, whilst further validation and optimization work would be beneficial, ASL-based estimation of CBF is widely used as a biomarker of hemodynamic stress in both observational studies and treatment trials in SCD patients, with several studies demonstrating sensitivity to change.…”
Section: Quantitative Imaging In Steady-state Settingsmentioning
confidence: 99%